INOVASI HERBAL BALM DARI EKSTRAK JERIANGAU (ACORUS CALAMUS): TINJAUAN POTENSI MEDIS PENDUKUNG SEBAGAI AROMATERAPI DAN PEREDA NYERI: Pemanfaatan Herbal Sebagai Bahan Baku Terapi Suportif - Rahmaddiansyah, Refa; Rahmi, Wahida; Yurensi, Nisriinaa; Rita, Rauza Sukma (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2024)
Background: Indonesia is an area that has various types of medicinal plants, but until now only about 1,200 species are used as raw materials for traditional medicines or herbs. A. calamus (Acoraceae) or jeriangau is a medicinal plant that has a rhizome. Jeriangau is used as a raw material for traditional medicine for various therapeutic purposes. This is because jeriangau contains chemical glycosides, flavonoids, saponins, tannins, polyphenols, and essential oils that can be used as aromatherapy. Discussion: Jeriangau is an annual herb used as a traditional medicine. This plant is an aromatic plant with a spicy taste. Jeriangau rhizome has anti-spasmodic, aromatic, expectorant, anti-nausea, sedative properties, stimulant effects, mental illness, diarrhea, and bronchitis. Jeriangau essential oil serves as a pain reliever for toothaches and headaches. The rhizome of the Jeriangau plant contains 1,2,4-trimethoxy-5-(1-prophenyl)-benzene essential oil or better known as asarone. Asarone is the main content in leaves while acorenon is the main content in rhizomes. It suggests the presence of atropine-like anticholinergic effects. Jeriangau compound has analgesic, sedative and neurodepressive properties which can have a sedative effect. In neonates with diarrhea, the spasmolytic and antisecretory effect of the extract can reduce the frequency of watery bowel movements, inhibitory responses to different spasmogens, and airway relaxation. Conclusion: Jeriangau with essential oil and several bioactive components such as asarone and isocalamendiol has the potential as a pain reliever and aromatherapy